New signatures of the spin gap in quantum point contacts - K. L. Hudson (Nature Portfolio, 2021)
In one-dimensional systems, the combination of a strong spin-orbit interaction and an applied magnetic field can give rise to a spin-gap, however experimental identification is difficult. Here, the authors present new signatures for the spin-gap, and verify these experimentally in hole QPCs.